2000
DOI: 10.1034/j.1600-0420.2000.078003369.x
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir delivery through an intravitreal microdialysis probe in rabbit

Abstract: ABSTRACT.The treatment of cytomegalovirus retinitis has during the last years been done mainly with sustained release ganciclovir devices implanted in the vitreous. In the present study it is shown that ganciclovir can be administered into the rabbit vitreous by microdialysis. A concentration of about 10 ª6 M, which is considered within the therapeutic range, is achieved in the vitreous after a microdialysis perfusion. The method offers possibility of variation in the drug delivery that is not possible with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The problem of transport across the blood-retina barrier is particularly important for the treatment of cytomegalovirus retinitis. It was shown that MD could also be used to administer ganciclovir to the rabbit vitreous within the therapeutic range, offering a route of drug delivery that is not possible with conventional ganciclovir implants (178).…”
Section: Methods For Studies Of Target Site Drug Distribution In Antimentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of transport across the blood-retina barrier is particularly important for the treatment of cytomegalovirus retinitis. It was shown that MD could also be used to administer ganciclovir to the rabbit vitreous within the therapeutic range, offering a route of drug delivery that is not possible with conventional ganciclovir implants (178).…”
Section: Methods For Studies Of Target Site Drug Distribution In Antimentioning
confidence: 99%
“…To date, MD has been used to measure in animals the tissue PK of various antimicrobial agents, including quinolones (123,171), such as pefloxacin (171); chloramphenicol (160,161,168); ␤-lactams, such as cephalosporins, notably, cefazolin (165), cephalexin (166), cefotaxime (167), cefmetazole (162), cefuroxime (164), cephalothin (28), ceftriaxone (66,85,124,163), ceftazidime (66,169,178), cephaloridine (170), cefamandole (194), cefoperazone (29), and cefaclor (40); penicillins, notably, penicillin G (27), piperacillin and tazobactam (37,118), amoxicillin (148) (91), and stavudine (193), and of the antifungal agent fluconazole (191,192).…”
Section: Methods For Studies Of Target Site Drug Distribution In Antimentioning
confidence: 99%
“…Several other implants are also currently under investigation. Increasingly novel technologies, such as intravitreal microdialysis (3), are under investigation to deliver drugs within the eye. There currently exists no method to gauge the function of an implant at any time after implantation other than a tap of the aqueous or vitreous humor.…”
Section: Introductionmentioning
confidence: 99%
“…3The number of the animals examined can be kept to a low level contrary to traditional pharmacokinetic studies (simply blood collections) where every time point needs different animals. Moreover, MD not only offers the possibility of sampling from certain tissues but also of delivering drugs directly to the site of action (retrodialysis) [32,53,54] contrary to complementary techniques (see the next section). The experiments can be performed not only in anesthetized but also in freely moving animals 6.…”
Section: Advantages and Limitations Of Microdialysis Techniquesmentioning
confidence: 99%